Subdued global growth, restrained European expansion - Ferdinand Fichtner; Guido Baldi; Christian Dreger; Hella Engerer; Stefan Gebauer; Michael Hachula; Malte Rieth (DIW Economic Bulletin, 2016)
Global economic growth remains subdued. Leaving our forecast for this year unchanged, the pace of growth is expected to stand at 3.2 percent in 2016 and to increase somewhat over the following two years. In the advanced economies, the main growth driver will continue to be private consumption, which in turn is supported primarily by a steadily improving labor market and increases in real incomes. In Europe, the uncertainty associated with the Brexit decision will have a dampening effect on growth. In the emerging markets, the moderate increase in the pace of expansion should continue. In Russia and Brazil, the economic contraction process will gradually come to a halt, while in China, the current growth rate will remain stable thanks to solid consumer demand. Nevertheless, there are still a number of risks for the global economy: in particular, there's the uncertainty related to the Brexit decision, and tensions remain high in some parts of the European banking sector.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook